Fungal Infections in Immunocompromised Hosts - Kontoyiannis, Dimitrios P. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book is a printed edition of the Special Issue Fungal Infections in Immunocompromised Hosts that was published in JoF